Genetic analysis of embryonic cis-acting regulatory elements of the Drosophila homeotic gene Sex combs reduced. - Gorman, M.J.; Kaufman, T.C. (Genetics, 1995)
The homeotic gene Sex combs reduced (Scr) of Drosophila melanogaster is expressed in the labial and prothoracic segments of the ectoderm, in parasegments two and three of the CNS, and in the visceral mesoderm of the anterior and posterior midgut. The mutationally defined function of Scr is to specify the identity of the labial and prothoracic segments and to control the development of the gastric caeca. The Scr locus occupies a chromosomal region of approximately 80 kb within the Antennapedia complex (ANT-C). To understand how Scr's spatiotemporal expression pattern is generated in the embryo, we have mapped its transcriptional regulatory elements using three approaches. First, we examined the expression pattern of Scr in embryos containing chromosomal rearrangements that remove potential Scr regulatory elements. Second, we made and analyzed a set of Scr minigene transformants. Third, we analyzed a set of Scr-lacZ enhancer tester constructs. Using more sensitive anti-SCR antisera, we discovered that Scr is expressed in tissues that were not previously thought to accumulate SCR: a stripe of ectodermal cells in the parasegment 2 region of stage 5 embryos, the embryonic salivary glands, and the dorsal ridge. Four DNA fragments that had previously been shown in an analysis of Scr-lacZ reporter constructs to contain putative Scr enhancer elements were found to have functional enhancers; similarly, another Scr fragment was found to contain a functional repressor. Our results suggest that regulation of Scr in the labial segment and the CNS requires the apparently synergistic action of multiple, widely spaced enhancer elements. Regulation in the prothorax also appears to be controlled by multiple enhancers:one complete pattern element and one subpattern element. In contrast, Scr regulation in the visceral mesoderm is controlled by an enhancer(s) located in only one DNA fragment.